An Optical View of Extragalactic γ-Ray Emitters - Paiano, Simona; Falomo, Renato; Landoni, Marco; Treves, Aldo; Scarpa, Riccardo (Frontiers in Astronomy and Space Sciences, 2017)
The Fermi Gamma-ray Observatory discovered about a thousand extragalactic sources emitting energy from 100 MeV to 100 GeV. The majority of these sources belong to the class of blazars characterized by a quasi-featureless optical spectrum (BL Lac Objects). This hampers the determination of their redshift and therefore hinders the characterization of this class of objects. To investigate the nature of these sources and to determine their redshift, we are carrying out an extensive campaign at the 10m Gran Telescopio Canarias to secure high signal-to-noise ratio optical spectra. These observations allow us to confirm the blazar nature of the targets, to find new redshifts or to set stringent limits on the redshift based on the minimum equivalent width of absorption features expected from their host galaxy, assuming it is a massive elliptical galaxy.These results are of importance for the multi-frequencies emission models of the blazars, to test their extreme physics, to shed light on their cosmic evolution and abundance in the far Universe.These gamma emitters are also of great importance for the characterization of the extragalactic background light through the absorption by the IR-optical background photons.